Full-band frequency-integrated antenna monitoring system - Khymych, H. P.; Umzar, Yu. A.; Tkachenko, V. F. (Видавництво Національного університету "Львівська політехніка", 2009)
The paper presents full-band frequency-integrated antenna monitoring system. Module optimization of full-band structures is conducted on the basis of the use of different type antennas for some separate basic frequency ranges (modules), which in the process of the integration create the integrated full-band system with the maximum factor of the use of effective capacity.
Keywords: Ka-band; antenna; double-reflector antenna